(untitled) (LEARNing Landscapes, 2021)
Drawing upon Heron and Reason’s (1997) participatory inquiry paradigm and extended epistemology, this article explores how six Master of Social Work (MSW) students engaged in sensory arts-based critical reflection concerning their social location, identities, social justice, and social policy. We share our process for creating sensory arts-based stories, the stories themselves, and pedagogical reflections. We elucidate how sensory arts-based storytelling allows learners to draw upon their strengths, unique perspectives, and experiences in the world, generating transformative understandings of social justice. Sensory arts-based storytelling holds potential as an interdisciplinary mode of critical reflection, generating inclusive learning environments oriented towards social change.